2000
DOI: 10.1021/ic000288t
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Manipulation of Photoexcited State Relaxation in (bpy)2RuII(binicotinic acid)

Abstract: The emission spectrum and luminescent lifetime of (bpy) 2 Ru II (binicotinic acid) is affected by the presence of heavy metal ions in solution. As little as 1 µM Pb 2+ causes a red shift in emission, an increase in the emission quantum yield, and an increase in the room-temperature lifetime. A smaller red shift is observed in the 4,4′dicarboxy analogue in the presence of large quantities of lead; however, the emission lifetime and intensity are dimished. An X-ray determination of the ground-state geometry show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(50 citation statements)
references
References 19 publications
2
48
0
Order By: Relevance
“…13 On the basis of spectroscopic and X-ray crystallographic studies on an Ru(II) complex having 3,3′-R2-bpy (R = COOH), Perkovic reported that the emission quantum yield of the complex with large structural distortion became very low, as compared with that of a complex having the Oh symmetry. 6 Therefore, we think that the very low-emission quantum yield of Ru(bpy)2(CE-bpy) 2+ can be ascribed to the distorted structures of the complex as described in the preceding section.…”
Section: Spectroscopic Study Of Ion Recognition By Ru(bpy)2(ce-bpy) 2+mentioning
confidence: 87%
See 2 more Smart Citations
“…13 On the basis of spectroscopic and X-ray crystallographic studies on an Ru(II) complex having 3,3′-R2-bpy (R = COOH), Perkovic reported that the emission quantum yield of the complex with large structural distortion became very low, as compared with that of a complex having the Oh symmetry. 6 Therefore, we think that the very low-emission quantum yield of Ru(bpy)2(CE-bpy) 2+ can be ascribed to the distorted structures of the complex as described in the preceding section.…”
Section: Spectroscopic Study Of Ion Recognition By Ru(bpy)2(ce-bpy) 2+mentioning
confidence: 87%
“…3 As another way to incorporate a crown-ether moiety to bpy, we focused our attention on 3,3′-disubstituted-2,2′-bipyridine (3,3′-R2-bpy) and its ruthenium(II) complex. [5][6][7][8] In free 3,3′-R2-bpy, the R orient to trans with respect to one another, owing to a steric hindrance between R. When 3,3′-R2-bpy coordinates to a ruthenium ion, its structure becomes more or less distorted from octahedral (Oh) symmetry because of a steric repulsion between the Rs. 5,6 Such a circumstance in the complex brings about a non-emissive or weakly emissive property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39,40] These effects are much more important in the case of 3,3'-functionalized bipyridyl-Ru II complexes compared to 4,4'-functionalized analogues. [41] Indeed, steric repulsion between substituents at the 3,3'-positions of a bipyridyl ligand induces an angular twist about the carboncarbon bridge head. This angle is responsible for the disruption of the p conjugation of the bipyridyl ligand and disfavors the charge transfer between the metal center and the bipyridyl ligands.…”
Section: Introductionmentioning
confidence: 99%
“…This angle is responsible for the disruption of the p conjugation of the bipyridyl ligand and disfavors the charge transfer between the metal center and the bipyridyl ligands. [41,42] Our approach is based on the structural changes induced by the anions bonding and the resulting modification of luminescence signals. Taking into account the crucial importance of hydrogen bonding and electrostatic interactions in anion recognition, guanidinium moieties [43,44] were chosen as anion binding functions.…”
Section: Introductionmentioning
confidence: 99%